Prevalence of anxiety, depression, and stress among teachers during the COVID-19 pandemic: A PRISMA-compliant systematic review. Issue 44 (5th November 2021) - Silva, David Franciole Oliveira; Cobucci, Ricardo Ney; Lima, Severina Carla Vieira Cunha; de Andrade, Fábia Barbosa
Abstract: Background: Identifying the prevalence of anxiety, depression, and stress among teachers during the COVID-19 pandemic. Methods: Systematic review of original studies published in any language. Protocol published in PROSPERO under number CRD42021240543. The search was carried out in the Web of Science, PsycINFO, Pubmed, Embase, LILACS, and SciELO databases, using the descriptors: anxiety, depression, stress, teacher, faculty, COVID-19, and their synonyms. Narrative synthesis was carried out in line with the synthesis without meta-analysis in systematic reviews. Results: Of the 1372 records identified, 6 studies, all cross-sectional, were included in the review. The studies were carried out in China, Brazil, the United States of America, India, and Spain. Five studies included more women than men. The participants were aged from 24 to 60 years. Three studies included only school teachers, 2 included schools and universities teachers, and 1 only university teachers. Of the 5 studies, all dealt with remote activities and only 1 included teachers who returned to face-to-face classes 1 to 2 weeks ago. The prevalence of anxiety ranged from 10% to 49.4%, and depression from 15.9% to 28.9%, being considerably higher in studies with teachers who worked in schools. The prevalence of stress ranged from 12.6% to 50.6%. Conclusion: The prevalence of anxiety, depression, and stress was high among teachers during the pandemic, with great variation between studies. Anxiety and stress were more prevalent in the Spanish study. The results show the need for measures for the care of teachers' mental health, especially when returning to face-to-face classes.